RETRACTED: Green economy as a factor of sustainable development of the state - Kuzubov Alexey; Maksimenko Aleksandr; Tekucheva Svetlana; Yureva Viktoria (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001